Moka [videorecording (DVD)] - Mermoud, Frédéric; Devos, Emmanuelle; Baye, Nathalie, 1948-; Rosnay, Tatiana de, 1961- (Film Movement series., 2017)
Diane Kramer is led by one obsession: to find the driver of the mocha color Mercedes which hit her son and devastated her life. With a few belongings, some money and a gun, she goes to Evian, where she's learned the driver lives.